Flavonoid compounds of tapak liman plant (Elephantopus scaber) as antihyperuricemia - Neni Sri Gunarti; Himyatul Hidayah (Universitas Islam Indonesia, 2022)
Abstract Background: Hyperuricemia is a condition where uric acid levels in the blood increase more than 6 mg/dL. Tapak liman (Elephantopus scaber) contains flavonoid compounds that are reported to inhibit the activity of the xanthine oxidase enzyme that causes hyperuricemia. Several Asteraceae tribes have activity as antihyperuricemia, one of which is the tapak liman plant (E. scaber) because of the compounds contained in the flavonoid group which has a working mechanism as an inhibitor of the xanthine oxidase enzyme.Objective: To determine the types of flavonoid compounds in tapak liman (E. scaber) plants that have antihyperuricemic activity.Method: This research is qualitative research using Literature Review Article (LRA) using Google Scholar, PubMed, ResearchGate, and Science direct databases with keywords related to the research topic, namely